Jurisprudential and Legal Thought on Article 401 of the Civil Law - S. M. Mahdi Ghabooli Dorafshan; Mahdieh Latifzadeh (آموزه‌‌های فقه مدني)
Option of condition is one of the options which relates to the agreement of the parties to the contract. One of the important issues regarding this option, is the time of option of condition which is in article 401 of the Civil Law, following a group of jurisprudents, has considered the indefinite time causes the void of the contract and the condition and a group of jurists have joined the agreement on the unknown time in following the jurisprudential texts. Now the question is whether the rule is based on strong basics and reasons or not? In particular, contracts are often neglected or neglected in determining of option of condition contracts. This study, by examining various jurisprudential and legal opinions and reviewing the evidence and reasons, concludes that both parties’ silence on the term of condition option and the more correct view is the validity of the condition and the contract where there is a criterion for determining the term, so it is suggested to amend and supplement the civil law in this field.